Functional Characterization of Ly49+CD8 T-Cells in Both Normal Condition and During Anti-Viral Response - Shytikov, Dmytro; Rohila, Deepak; Li, Dan; Wang, Pengfei; Jiang, Mei; Zhang, Mingxu; Xu, Qin; Lu, Linrong (Frontiers in Immunology, 2021)
The role of Ly49+CD8 T-cells in the immune system is not clear. Previously, several papers suggested Ly49+CD8 T cells as immunosuppressors, while multiple studies also suggested their role as potent participants of the immune response. The mechanism of Ly49 expression on CD8 T-cells is also not clear. We investigated phenotype, functions, and regulation of Ly49 expression on murine CD8 T-cells in both normal state and during LCMV infection. CD8 T-cells express different Ly49 receptors compared with NK-cells. In intact mice, Ly49+CD8 T-cells have a phenotype similar to resting central memory CD8 T-cells and do not show impaired proliferation and cytokine production. Conventional CD8 T-cells upregulate Ly49 receptors during TCR-induced stimulation, and IL-2, as well as IL-15, affect it. At the same time, Ly49+CD8 T-cells change the Ly49 expression profile dramatically upon re-stimulation downregulating inhibitory and upregulating activating Ly49 receptors. We observed the expression of Ly49 receptors on the virus-specific CD8 T-cells during LCMV infection, especially marked in the early stages, and participation of Ly49+CD8 T-cells in the anti-viral response. Thus, CD8 T-cells acquire Ly49 receptors during the T-cell activation and show dynamic regulation of Ly49 receptors during stimulation.